Metabolic, hormonal and performance effects of isomaltulose ingestion before prolonged aerobic exercise: a double-blind, randomised, cross-over trial - Hannah L. Notbohm; Joshua F. Feuerbacher; Finn Papendorf; Nils Friese; Mats W. Jacobs; Hans-Georg Predel; Jonas Zacher; Wilhelm Bloch; Moritz Schumann (Taylor & Francis Group, 2021)
Background Isomaltulose has been discussed as a low glycaemic carbohydrate but evidence concerning performance benefits and physiological responses has produced varying results. Therefore, we primarily aimed to investigate the effects of isomaltulose ingestion compared to glucose and maltodextrin on fat and carbohydrate oxidation rates, blood glucose levels and serum hormone concentrations of insulin and glucose-dependent insulinotropic polypeptide (GIP). As secondary aims, we assessed running performance and gastrointestinal discomfort. Methods Twenty-one male recreational endurance runners performed a 70-min constant load trial at 70% maximal running speed (Vmax), followed by a time to exhaustion (TTE) test at 85% Vmax after ingesting either 50 g isomaltulose, maltodextrin or glucose. Fat and carbohydrate oxidation rates were calculated from spiroergometric data. Venous blood samples for measurement of GIP and insulin were drawn before, after the constant load trial and after the TTE. Capillary blood samples for glucose concentrations and subjective feeling of gastrointestinal discomfort were collected every 10 min during the constant load trial. Results No between-condition differences were observed in the area under the curve analysis of fat (p = 0.576) and carbohydrate oxidation rates (p = 0.887). Isomaltulose ingestion led to lower baseline postprandial concentrations of blood glucose compared to maltodextrin (percent change [95% confidence interval], − 16.7% [− 21.8,-11.6], p < 0.001) and glucose (− 11.5% [− 17.3,-5.7], p = 0.001). Similarly, insulin and GIP concentrations were also lower following isomaltulose ingestion compared to maltodextrin (− 40.3% [− 50.5,-30.0], p = 0.001 and − 69.1% [− 74.3,-63.8], p < 0.001, respectively) and glucose (− 32.6% [− 43.9,-21.2], p = 0.012 and − 55.8% [− 70.7,-40.9], p < 0.001, respectively). Furthermore, glucose fluctuation was lower after isomaltulose ingestion compared to maltodextrin (− 26.0% [− 34.2,-17.8], p < 0.001) and glucose (− 17.4% [− 29.1,-5.6], p < 0.001). However, during and after exercise, no between-condition differences for glucose (p = 0.872), insulin (p = 0.503) and GIP (p = 0.244) were observed. No between-condition differences were found for TTE (p = 0.876) or gastrointestinal discomfort (p = 0.119). Conclusion Isomaltulose ingestion led to lower baseline postprandial concentrations of glucose, insulin and GIP compared to maltodextrin and glucose. Consequently, blood glucose fluctuations were lower during treadmill running after isomaltulose ingestion, while no between-condition differences were observed for CHO and fat oxidation rates, treadmill running performance and gastrointestinal discomfort. Further research is required to provide specific guidelines on supplementing isomaltulose in performance and health settings.